Concept of building a modeling complex study of the influence of individual characteristics an aircraft on its flying characteristics - Іщенко, С. О.; Семігківська, Т. О. (Proceedings of National Aviation University (archive), 2020)
The use of mathematical models of aircraft for research is considered the reasons for the appearance in them of individual characteristics and the degree of their influence on the flight characteristics Ristiki The structure of a universal mathematical model and the purpose of MIC modules, which provides identification of the individual flight characteristics of any type of aircraft.